Global diversification strategy, transformational leadership and their relationship to the sustainability performance of Malaysian state-owned enterprises / M. Anuar Abdullah - Abdullah, M. Anuar (2019)
The concept of business sustainability or business resilient or lifelong business is quite unpopular among business practitioners and academicians before the year 1990. Moreover, the 1960s have seen most of business researches concentrating so much on productivity, performance, and profitability. These have short lived as a few series of economic downturns affected most of the very profitable and successful companies worldwide, and as a result; they turned into problematic companies. This incident has prompted many business shareholders and corporate leaders to give more priority to business sustainability, instead of productivity, performance and profitability. In Malaysia, the South East Asia economic crisis of currencies that happened in mid of 1997-1998 had badly affected many companies, especially state-owned enterprises (SOEs), and many of them went bankrupt. Following this crisis was the sub-prime crisis in the United State of America (USA) in 2008 – 2009, that also indirectly affected our SOEs. Malaysian SOE sustainability performance is at critical levels, hence the study on this topic is crucial to be carried out. Due to their socio-economic importance to the country, this study has therefore targeted the study on managers’ perception, especially on the topic of the corporate strategy and leadership in order to achieve sustainable performance. The study mainly aimed to understand the perceptions of Malaysian SOEs’ managers with reference to global diversification strategy (GDS), and mediated by transformational leadership (TL) as a way to achieve sustainable performance (SHP) SOEs. The resource-based theory, internationalization theory and transformational leadership theory have been theoretical foundations for this study in an attempt to enhance the existing conceptual model. The data for this study was collected from the population of 61 Malaysian SOEs, using drop-off and collect technique. From nine hypotheses tested, eight of them were significant and only one was not significant. GDS positively affected the sustainability performance (SHP) of Malaysian SOEs. Strategic transformational leadership (STL) is identified as a mediating factor in the relationship between GDS and SHP. This finding also constitutes the strategic recommendation to the Malaysian SOEs about the importance of sustainable competitive advantage (SCA) as they are in the midst of facing competition at the global arena. Furthermore, the findings have established an empirical foundation for future research.